Hematologic health and athletic performance: exploring the role of anemia. A systematic review of clinical studies - Blecharz , Gabriela; Szwech, Julia; Baran, Karolina; Jańczyk, Natalia; Mędrysa, Karolina; Pokrzepa, Jakub; Presak, Michał; Winkowska, Alicja; Jankowska, Marlena; Bartnik, Katarzyna (Quality in Sport, 2025)
Introduction Anemia is a widespread hematological disorder characterized by low hemoglobin levels, which reduce the blood’s capacity to deliver oxygen to tissues. Iron deficiency, its leading cause, is essential for hemoglobin synthesis, myoglobin function, and energy production. While anemia can manifest in various forms, its impact on athletic performance remains a subject of ongoing research. Given the increasing prevalence of anemia among athletes, especially in endurance sports, understanding its effects on physical performance is essential for developing effective training and treatment approaches. Aim of the study The aim of the study was to analyze the impact of anemia on the physical performance of athletes, the effectiveness of iron supplementation and differences in the response to anemia in various sports groups. Materials and methods The article was created based on the PubMed and Cochrane databases. The literature was analyzed using the fallow keywords: anemia, athletes, sport, physical performance, hemoglobin, exercise tolerance, oxygen delivery. Results Anemia, particularly iron deficiency, significantly limits athletes’ physical performance, especially in endurance sports where oxygen transport is crucial. Treatment with iron supplementation improves performance, but an individualized approach considering factors like gender, age, and sport type is necessary. Conclusion Effective diagnosis and treatment of anemia can enhance athletic performance. Regular hematological monitoring, personalized dietary strategies, and appropriate iron supplementation are recommended. Educating athletes, coaches, and medical staff on anemia prevention is essential for optimizing training and performance. Key words Anemia, athletes, sport, physical performance, hemoglobin, exercise tolerance, oxygen delivery.